Reduction of Initial Corrosion Rate and Improvement of Cell Adhesion Through Surface Modification of Biodegradable Mg Alloy - Han, Hyung-Seop; Lee, Sun Hee; Kim, Won-Joo; Jeon, Hojeong; Seok, Hyun-Kwang; Ahn, Jae-Pyung; Kim, Yu-Chan (대한금속·재료학회, 2015)
In this study, the surface modification of biodegradable pure Magnesium and Mg-5wt%Ca-1 wt%Zn alloy was performed through immersion in HBSS, inorganic salt solution and cell media to reduce initial hydrogen evolution and improve cell adhesion. The formation of different CaP-like coatings from immersion of pure Mg and Mg alloy were observed using Cryo FM analysis and their performances were measured through cell adhesion, quantification of released Mg ions, and cell cytotoxicity assays. The coating layers displayed significant reduction of initial corrosion rate, and cell adhesion for both pure Mg and Mg alloy appeared to be influenced by the amino acids and proteins in the cell media. In general, Mg alloy showed a denser coating layer with higher Ca contents, resulting in greater reduction of initial corrosion rate and improved cell adhesion, when compared to pure Mg. This is due to saturation of Ca around the corrosion site that provided much favorable environmental condition to produce denser calcium phosphate coating mixture. The result from this study suggests that the surface modification of biodegradable Mg alloy by immersion in alkaline solutions can be utilized to obtain ideal biodegradable orthopedic implant material with reduced initial hydrogen evolution rate and improved cell adhesion.